2002
DOI: 10.1055/s-2002-35276
|View full text |Cite
|
Sign up to set email alerts
|

Differente Muster regionaler Hirnaktivität nach emotionaler Stimulation bei alexithymen Patienten im Vergleich zu Normalpersonen

Abstract: During emotional autobiographic recall, alexithymia, either trait or state, is characterized by utilization of different brain regions when compared to normal controls. The areas activated by alexithymic persons largely comprise of language related regions, leaving out limbic and paralimbic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 15 publications
(22 reference statements)
1
11
0
2
Order By: Relevance
“…Thus, their results suggest that alexithymia is related to less ACC activation. In line with this, Huber et al (2002) and Kano et al (2003), using PET, both demonstrated that alexithymics showed less activation in the anterior cingulate cortex than nonalexithymics, while looking at angry faces or during autobiographical recall of emotional situations. Berthoz et al (2002) obtained results that are more complicated.…”
Section: Alexithymia and The Anterior Cingulatesupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, their results suggest that alexithymia is related to less ACC activation. In line with this, Huber et al (2002) and Kano et al (2003), using PET, both demonstrated that alexithymics showed less activation in the anterior cingulate cortex than nonalexithymics, while looking at angry faces or during autobiographical recall of emotional situations. Berthoz et al (2002) obtained results that are more complicated.…”
Section: Alexithymia and The Anterior Cingulatesupporting
confidence: 58%
“…Furthermore, these authors failed to find this relationship in females. Huber et al (2002) demonstrated in a PET study that alexithymic subjects showed less activation in the corpus callosum in response to emotional stimuli compared to nonalexithymics. However, Kano et al (2003), who also measured brain activity using PET, reported the opposite result.…”
Section: Alexithymia and The Corpus Callosummentioning
confidence: 99%
“…An anatomical or functional alteration in one of these regions and its underlying pharmacology could therefore affect other linked functions [52,53,54]. Several neuroimaging studies point to significant functional [50,55,56,57] and anatomical [58] alterations in the right anterior cingulate cortex, posterior cingulate cortex [59] and in other prefrontal areas [50, 56, 57] as well as in the corpus callosum [55] of alexithymic subjects during emotional processing. In normal subjects, Critchley et al [60] showed that the anterior cingulate cortex is involved in the regulation of autonomic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Während negativer Affektinduktion sind bei Hochalexithymen verglichen mit Niedrigalexithymen insbesondere verminderte Aktivitäten in umschriebenen Arealen des medialen präfrontalen Kortex (Brodmann-Area 9) [25,26] Originalarbeit turen signifikant häufiger bei den Normalpersonen aktiviert waren. Leider wurde in dieser Studie die Depressivität nicht hinreichend kontrolliert.…”
Section: Introductionunclassified